Effects of acute ammonia toxicity on oxidative stress, DNA damage and apoptosis in digestive gland and gill of Asian clam (Corbicula fluminea). Issue 99 (April 2020) - Zhang, Tianxu; Yan, Zhenguang; Zheng, Xin; Wang, Shuping; Fan, Juntao; Liu, Zhengtao
Abstract: Ammonia is one of the major pollutants associated with the main river basins due to ammonification of uneaten food and animal excretion, which usually brings detrimental health effects to aquatic invertebrate. However, the mechanisms of ammonia toxicity in aquatic invertebrate have rarely been reported. In this study, C. fluminea was exposed to different levels of ammonia (control group, 10 mg/L, and 25 mg/L) for 24 h and 48 h, and digestive gland and gill were collected to explore toxic effects on oxidative stress, DNA damage and apoptosis under ammonia stress. The results showed that ammonia poisoning could increase the activity of oxidative stress enzyme (SOD and CAT), inducing differentially expressed genes ( DRAM2, GADD45, P53, BAX, BCL2, CASP8, CASP9, CASP3, HSP70 and HSP90 ) and different cytokines (IL-1 beta, IL-8, IL-17 and TNF-alpha) of DNA damage and apoptosis. The difference of toxic effects induced by ammonia among digestive gland and gill were also observed by real-time PCR and TUNEL staining. Our results will be helpful to understand the mechanism of aquatic toxicology induced by ammonia in C. fluminea. Highlights: It's the first study on differential analysis of digestive gland and gill in Corbicula fluminea under ammonia stress. Oxidative stress, DNA damage and apoptosis were identified under ammonia stress. Oxidative stress related enzyme and HSPs were only partially successful in potentially minimizing the extent of apoptosis.